Aktivitas Antibakteri Ekstrak Bawang Hitam Variasi Waktu Aging Terhadap Pencegahan Dysbiosis Kulit Penyebab Jerawat: Antibacterial Activity of Black Garlic Extract Variations in Aging Time on Prevention of Skin Dysbiosis Causes Acne - Luthfia Hastiani Muharram; Fauzia Ningrum Syaputri; Wulan Pertiwi; Rizki Fika Saputri (Jurnal Sains dan Kesehatan, 2022)
Skin diseases, including acne, can be caused by a microbial imbalance (dysbiosis). The specific bacteria involved in acne dysbiosis are Cutibacterium (Propionibacterium) acnes and Staphylococcus epidermidis. Black garlic has better potential to be alternative antibiotic and chemical to curing ance and maintaining skin health, because it has antimicrobial potential and can inhibit the decrease in collagen deposition on the skin. These potentials can be alternative of antibiotics and chemicals to treat acne and maintain healthy skin. This study aimed to determine the antibacterial activity of black garlic extract against bacteria that cause acne dysbiosis. Garlic was aging with 3 variations of time (7, 14, and 21 days) then macerated with 70% alcohol and tested for antimicrobial activity to Cutibacterium acnes and Staphylococcus epidermidis with clindamycin as positive control. Black garlic extract provided inhibitory activity against Staphylococcus epidermidis and Cutibacterium acnes. The best recommendation time for aging garlic to prevent skin dysbiosis causes acne is 7 to 14 days.